2016
DOI: 10.1007/s10597-016-0074-7
|View full text |Cite
|
Sign up to set email alerts
|

Explanatory Models of Illness, Help Seeking Behaviours and Related Factors in Patients with Schizophrenia: A Comparative Study from Two Different Provinces of Turkey

Abstract: This study aims to identify the help seeking behaviours of patients from two geographically distinct provinces of Turkey. A questionnaire about sociodemographic characteristics and help seeking ways was applied to 49 schizophrenia patients from Van, 99 from Ankara. The ratio of patients seeking psychiatric help at the beginning of their illness was 76% in Ankara, the capital city, in contrast to 54% in Van (p = 0.01). Twenty-two percent of patients from Ankara and 69% from Van reported that non-psychiatric hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 33 publications
0
13
1
Order By: Relevance
“…Shi and colleague"s study in China showed that 63% of individuals with SZ first sought help from non-psychiatric medical sources [9]. Many previous studies found that 16% to 76% of individuals with SZ seek help from relatives, friends, traditional/faith healers and religion [10][11][12][13][14][15][16]. Moreover, the longer individuals have suffered from SZ, the lower their remission and recovery rates [17].Experiencing SZ without treatment can mean more serious damage to social functioning, one"s own physical health, and the safety of others [18][19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Shi and colleague"s study in China showed that 63% of individuals with SZ first sought help from non-psychiatric medical sources [9]. Many previous studies found that 16% to 76% of individuals with SZ seek help from relatives, friends, traditional/faith healers and religion [10][11][12][13][14][15][16]. Moreover, the longer individuals have suffered from SZ, the lower their remission and recovery rates [17].Experiencing SZ without treatment can mean more serious damage to social functioning, one"s own physical health, and the safety of others [18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the longer individuals have suffered from SZ, the lower their remission and recovery rates [17].Experiencing SZ without treatment can mean more serious damage to social functioning, one"s own physical health, and the safety of others [18][19]. Some research concludes that common choices for help include psychiatric hospitals [16], general hospitals [20], and psychotherapy [21]. Studies worldwide show that the most common first choices for individuals seeking help are general practitioners, traditional/faith healers and psychiatrists [20,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The top three choices of non-medical options include relatives, praying to Buddha, and traditional and/or faith healers. This study found psychiatric hospital and relatives to be the most common rst choices of individuals with SZ seeking help, whereas some studies show psychiatrists and psychiatric hospitals as the most common rst choices [16].Nonetheless, other studies show general medical hospitals and physicians as the rst choice [10,20]. Such disparity in ndings may arise from different medical structure and low accessibility of psychiatrists and mental hospitals.…”
Section: Discussion 1key Factors Determining Help-seeking Behavior Inmentioning
confidence: 74%
“…Shi and colleague's study in China showed that 63% of individuals with SZ rst sought help from non-psychiatric medical sources [9]. Many previous studies found that 16% to 76% of individuals with SZ seek help from relatives, friends, traditional/faith healers and religion [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%